The Utilization Of Coconut Tombong As A Raw Material For Flour - Siahaya, Griennasty Clawdya; Titaley, Samuel; Rehena, Zasendy (Agrikan Jurnal Agribisnis Perikanan, 2021)
The purpose of this study is to obtain a proper drying time in producing a nutrient-grade coconut tombong flour. This study used an experimental design with a complete randomized design where the coconut tombong was dried at 50Â°C for 6,7 and 8 hours. The results of the analysis showed that coconut tombong flour with 8 hours drying produced the best of coconut tombong flour compared with 6 and 7 hours drying, with lower moisture content 11, 7353%, fat 8,1666%, protein 11,7158%, ash content 7,4917% and crude fiber 11,8421%. The results of statistical test show that the drying treatment of 6, 7 and 8 hours gives a very significant difference to the average chemical properties (carbohydrate, moisture content, protein, fat, ash content, crude fiber) coconut tombong flour with Fvalue > Ftable 5% or significance value of all treatments is smaller than alpha value 0.05. Based on these results, it can be concluded that coconut tombong flour which through the drying process at 50Â°C for 8 hours (L3) is the best treatment among two other treatments (L1 and L2) which has the potential to be further developed as various substitution materials food products.